Meningkatkan Dimensi Bergotong Royong dalam Belajar PAK-BP dengan Model PBL Materi Pribadi Yang Tumbuh dan Berkembang Fase B Kelas IV SDN 16 Panoalatn - M. Indah Puspitarini; Fr. Wuriningsih; Budi Hartana (PROSIDING SEMINAR NASIONAL PENDIDIKAN DAN AGAMA, 2024)
The changes of the times may result in a shift in the values of life for individuals or even groups of people. However, most members of society who are not significantly affected by these changes continue to use "old ways." Good values from these traditional ways should indeed be preserved and developed by being passed down through generations, whether by communities that are far from modernization or those following contemporary progress. One long-standing tradition is the concept of mutual cooperation or "gotong royong." The dimension of mutual cooperation, as deepened in the Kurikulum Merdeka (Independent Curriculum), must be echoed both in schools and within society. In today's era, the spirit and values of mutual cooperation have diminished in some areas. Therefore, efforts are needed to further enhance this dimension. One way to deepen the Dimension of Mutual Cooperation is through Catholic Religious Education and Moral Education using the Problem-Based Learning model with five students at SDN 16 Panoalatn, aiming to improve the Dimension of Mutual Cooperation. In Cycle 1, the students’ development results showed 40% in the "Still Developing" category, 40% in the "Adequate" category, and 20% in the "Proficient" category, with none reaching the "Mastery" level (0%). Improvements were made in Cycle 2, with results showing 0% in the "Still Developing" and "Adequate" categories, 40% in the "Proficient" category, and 60% in the "Mastery" category for the Dimension of Mutual Cooperation.